2014
DOI: 10.5935/abc.20140126
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare-Associated Infective Endocarditis: Case Series in Referral Hospital from 2006 to 2011

Abstract: BackgroundHealthcare-associated infective endocarditis (HCA-IE), a severe complication of medical care, shows a growing incidence in literature.ObjectiveTo evaluate epidemiology, etiology, risk factors for acquisition, complications, surgical treatment, and outcome of HCA-IE.MethodsObservational prospective case series study (2006-2011) in a public hospital in Rio de Janeiro.ResultsFifty-three patients with HCA-IE from a total of 151 cases of infective endocarditis (IE) were included. There were 26 (49%) males… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
9
0
5

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 28 publications
2
9
0
5
Order By: Relevance
“…Our study found that IE was more common in men. This finding is in agreement with the studies by 7%); however, the prevalence in our study was higher than the rates of the disease noted in the studies by Parvisi et al (35%) and Francischetto et al (49%) (6)(7)(8)(9)(10)(11). The high prevalence rate might be attributed to intravenous drug users who were more common in men.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our study found that IE was more common in men. This finding is in agreement with the studies by 7%); however, the prevalence in our study was higher than the rates of the disease noted in the studies by Parvisi et al (35%) and Francischetto et al (49%) (6)(7)(8)(9)(10)(11). The high prevalence rate might be attributed to intravenous drug users who were more common in men.…”
Section: Discussionsupporting
confidence: 92%
“…In this study, 76% of the patients had fever, which is similar to the findings obtained by Reyahin et al (79.7%), but lower than those reported by Besharat et al (91%), Behzadnia et al (95%), and Francischetto et al (92%). It is possible that the patients had undergone antibiotic treatment before admission to our center (7,9,12).…”
Section: Discussionmentioning
confidence: 99%
“…The relatively low surgical intervention rate was somewhat unanticipated because non-population based, tertiary care referral studies have reported surgical rates close to 50% 18, 29, 30 . Over the study period in our investigation, there were 444 non-Olmsted County patients treated at Mayo Clinic Rochester, a large tertiary care referral center.…”
Section: Discussionmentioning
confidence: 99%
“…60 Our findings are in consonance with the results of a recent study showing that prior use of antibiotics is the main factor for the presence of infectious health care-associated endocarditis. 85 It can therefore be inferred that the current state of antibiotic therapy has reached a critical point because indiscriminate usage is leading to both compromised immunity and increased resistance.…”
Section: Extrinsic Rfs For Infectionmentioning
confidence: 99%